2005
DOI: 10.1073/pnas.0505047102
|View full text |Cite
|
Sign up to set email alerts
|

Targeting angiogenesis: Structural characterization and biological properties of a de novo engineered VEGF mimicking peptide

Abstract: Modulating angiogenesis is an attractive goal because many pathological conditions depend on the growth of new vessels. Angiogenesis is mainly regulated by the VEGF, a mitogen specific for endothelial cells. In the last years, many efforts have been pursued to modulate the angiogenic response targeting VEGF and its receptors. Based on the x-ray structure of VEGF bound to the receptor, we designed a peptide, QK, reproducing a region of the VEGF binding interface: the helix region 17-25. NMR conformation analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
291
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(308 citation statements)
references
References 47 publications
16
291
1
Order By: Relevance
“…The mutant PA again demonstrated no effect on VEGFR2 phosphorylation, establishing this as an ideal material control for the VEGF PA. Both the VEGF PA and the VEGF peptide signal similarly to the VEGF assay control for both receptors, confirming reports on the discovery of the epitope (30). Examining the effect of VEGF PA stimulation over time ( Fig.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The mutant PA again demonstrated no effect on VEGFR2 phosphorylation, establishing this as an ideal material control for the VEGF PA. Both the VEGF PA and the VEGF peptide signal similarly to the VEGF assay control for both receptors, confirming reports on the discovery of the epitope (30). Examining the effect of VEGF PA stimulation over time ( Fig.…”
Section: Resultssupporting
confidence: 71%
“…1C). The reported bioactive secondary structure of the VEGF-mimetic sequence is α-helical (30,31). CD of the VEGF PA revealed a signal characteristic of α-helix (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous study has shown that peptides can be synthesized to mimic the helical structure of a protein that interacts with its receptor to reproduce the biological activities of the full molecule (24). Upon further consideration, however, we reasoned that because helix B is amphipathic and of the 4-3 ␣-helix type, specific amino acid residues within the hydrophilic portion face the external, aqueous face (i.e., every fourth and third residue in the b and f position, respectively).…”
Section: Resultsmentioning
confidence: 99%